Prognostic heterogeneity of adult B‐cell precursor acute lymphoblastic leukaemia patients with t(1;19)(q23;p13)/TCF3‐PBX1 treated with measurable residual disease‐oriented protocols. (21st September 2021) - Ribera, Jordi; Granada, Isabel; Morgades, Mireia; González, Teresa; Ciudad, Juana; Such, Esperanza; Calasanz, María‐José; Mercadal, Santiago; Coll, Rosa; González‐Campos, José; Tormo, Mar; García‐Cadenas, Irene; et al.
Summary: The prognosis of t(1;19)(q23;p13)/transcription factor 3‐pre‐B‐cell leukaemia homeobox 1 ( TCF3‐PBX1 ) in adolescent and adult patients with acute lymphoblastic leukaemia (ALL) treated with measurable residual disease (MRD)‐oriented trials remains controversial. In the present study, we analysed the outcome of adolescent and adult patients with t(1;19)(q23;p13) enrolled in paediatric‐inspired trials. The patients with TCF3‐PBX1 showed similar MRD clearance and did not have different survival compared with other B‐cell precursor ALL patients. However, patients with TCF3‐PBX1 had a significantly higher cumulative incidence of relapse, especially among patients aged ≥35 years carrying additional cytogenetic alterations. These patients might benefit from additional/intensified therapy (e.g. immunotherapy in first complete remission with or without subsequent haematopoietic stem cell transplantation).